AB0231 Esophageal involvement in very early systemic sclerosis (SSC). (23rd January 2014) - Lepri, G.; Bellando Randone, S.; Serena, G.; Giani, I.; Carnesecchi, G.; Bruni, C.; Blagojevic, J.; Radicati, A.; Pucciani, F.; Matucci Cerinic, M.
Abstract : Background: SSc affects gastrointestinal tract in more than 80% of patients. Esophageal involvement is the most common manifestation with a prevalence ranging between 50 and 90%. Objectives: Evaluation of esophageal involvement and detection of its predictor factors in very early SSc patients. Methods: 56 patients (55 females), mean age 49, 2±14 years, with very early SSc were evaluated with esophageal manometry. The demographic data, esophageal symptoms (dysphagia, typical GERD symptoms), Raynaud phenomenon (presence/absence, duration), autoantibody profile (anticentromere antibodies [ACA], antinuclear antibodies [ANA], anti-Scl70 antibodies [Scl70]), videocapillaroscopy patterns (Normal, Early, Active, Late), puffy fingers, digital ulcers were recorded for all patients. Results: Esophageal body dysmotility (abnormal mean pressure of peristalsis or absence of peristalsis) was present in 49 patients (94, 2%), and was associated with a hypotensive lower esophageal sphincter (LES) in 26 (53, 1%). Esophageal symptoms were present in 26 patients (50%).Puffy fingers were present in 22 patients (42, 3%) and were associated with a smaller area of LES ( p-value: 0.011) . In 4 patients esophageal manometry was not performed because of scarce tolerance of the procedure. Conclusions: Esophageal disorders are frequently seen in very early SSc patients in particular in patients with puffy fingers. Disclosure of Interest: None Declared